Two new records of grasshopper (Orthoptera: Acridoidea) in China - Chen, Jian-Yu; Liu, Yu-Xian; Yang, Jin-Chen; Wang, Shao-Shan; Li, Xin-Jiang (Zootaxa, 2026)
Two grasshopper species, Dericorys albidula Serville, 1838 and Thrinchus arenosus Bey-Bienko, 1948, are reported as new records for China. Although they belong to different families, they share similar habitat preferences. Detailed morphological redescriptions and biological notes are provided for both species.